(untitled) (Revista Sapiência: sociedade, saberes e práticas educacionais (2238-3565), 2015)
This paper presents the reconfiguration of state, corporate and labour relations that follow from the increased international investment by oil companies in Brazil’s (bio)ethanol sector. It emphasises how new path-dependent technological and institutional arrangements, conceptualised as a ‘techno-institutional fix’, interrelate with broader systemic power relations and spatial strategies of accumulation (the spatial fix). These overlap to ensure competitive advantage of agroenergy leaders and increasingly concentrate land, wealth and power in the region of focus, albeit through accumulation strategies that postpone crises rather than resolve inherent instability. Testimonies from landless workers, rural and industrial workers in the fields and factories of biofuel cultivation and distillation counter the institutional discourse linking rural and sustainable development to these new energy extractions. The relatively fixed geographical nature of these workers’ collective organisations, however, is a marked contrast to the increasing flexibility and scales of operation of the leading multinational corporations and limits their capacity to resist prevailing relations. Resulting power asymmetries or ‘power geometries’ underscore the reproduction of inequality, labour exclusion and dispossession in the new frontiers of agroenergy production.